Impact Assessment of Skill Development Training on Low Cost Mushroom Production Technology in Panipat District of Haryana - Singh, Satpal; Garg, Rajbir; Malik, J S; Bhakar, Sandeep; Chander, Subhash (Indian Journal of Extension Education, 2021)
The present study was undertaken to assess the impact of skill development training about Low Cost MushroomÂ Production Technology as an enterprise on knowledge gain. A total number of 90 trainees who have undergone through five days skill development training at Krishi Vigyan Kendra, Panipat were selected as a sample for theÂ study. The impact of training programme was assessed by pre and post evaluation testing in terms of improvementÂ in knowledge on various aspects of Low Cost Mushroom Production Technology. It was observed that pretraining knowledge score was not much satisfactory for all the aspects of training programme. However, the knowledge score gained by respondents after training was more satisfactory in all aspects. The study revealed that experience to training had increased the knowledge of SC/ST Farm Women and Rural Youth regarding LowÂ Cost Mushroom Production Technology. In pre-evaluation test, the knowledge range of different participants was 4.4 per cent regarding Insect-Pest & Disease of mushroom and its management to 46.6 per cent in case of knowledge nutritional importance of mushrooms. Post training score of various practices ranged from 86.6 perÂ cent in case of chemical used for sterilization of casing mixture to 100 per cent in case of various practices likeÂ nutritional status of mushroom, method of spawning, method of casing, moisture Content in prepared Compost, Seed rate i.e. spawn required for 100 kg prepared compost, harvesting Method, Number of days for harvesting,Â value addition of Mushroom, marketing channel, storage of Mushroom, Number of days required for pin head initiation etc.